The Impact of E-Management on the Quality of Health Services: A Field Study at Sabha Medical Centre - Mansour, Jabar; Shabl, Khaled; Mashmoor, Moammar; Al-Saadi, Ahmed; Mashmoor, Hassan (Journal of Pure & Applied Sciences, 2025)
This study explores the role of e-management in enhancing the quality of healthcare services at Sabha Medical Centre, focusing on its reliance on human, technical, and administrative elements, as well as the requirements for programmes and networks. A descriptive-analytical method was employed, with a structured questionnaire distributed to a sample of 202 participants, achieving a response rate of 75%. The results of the reliability analysis indicated strong consistency, with Cronbach’s alpha values exceeding 0.7 for all studied variables. The findings suggest that e-management can significantly improve the quality of healthcare by streamlining processes, reducing errors, and ensuring timely service delivery. However, several notable gaps were identified, including insufficient training for staff, limited adoption of advanced technologies, and a lack of specialised administrative support for e-management systems. Regression analysis highlights important relationships between the quality of healthcare services and factors such as database accessibility, human resource readiness, and technical infrastructure, with statistically significant results across multiple variables (p < 0.05). The study emphasises the necessity of strategic investment in training programmes, enhancement of IT infrastructure, and the implementation of necessary administrative reforms to ensure optimal utilisation of e-management. It also offers practical recommendations to address the identified gaps and effectively integrate e-management systems, thereby contributing to improved quality of healthcare services and increased operational efficiency at Sabha Medical Centre.